Students’ Subjectness, Self-Efficacy and Psychological Well-Being: Comparative Research of Russian and Kazakhstan Students - V. G. Maralov; A. D. Kariyev; O. V. Krezhevskikh; M. A. Kudaka; L. E. Ageeva; E. N. Agranovich (Высшее образование в России)
The relevance of the study is due to the need to resolve the contradictions between the requirements of higher education for the personality of a young person and his real capabilities, manifested in the ability or inability to be the subject of his activity and his development. The need to resolve this contradiction has determined the purpose of this study – to identify the level of expression and structure of the subjective properties of students’ personality, their relationship with self-efficacy and psychological well-being. The work used a set of theoretical and empirical research methods, in particular, questionnaires to identify the level of an individual subjectivity development (M.A. Shchukina), general and social self-efficacy (M. Sherer and J. Maddux, adaptation by A.V. Boyarintseva), psychological well-being (K. Riff, adaptation by T.D. Shevelenkova and P.P. Fesenko). Mathematical processing was carried out using the criterion ϕ* – Fisher’s angular transformation, as well as methods of correlation analysis using the linear Pearson correlation coefficient. The subjects were students of a number of universities of the Russian Federation and the Republic of Kazakhstan. A total of 277 students majoring pedagogy and psychology took part in the study, among them 266 (96%) women, 11 (4%) men, average age 19.5 years (SD=1.5). As a result, no fundamental differences were revealed in the structure and manifestations of subjectivity depending on the place of residence, national and cultural traditions, which indicates the existence of some general patterns in the formation of the subjectivity of a future teacher or psychologist. A high level of subjectivity was identified in 57.04% respondents, medium – in 38.98%, low – in 3.98%. It has been established that the level of subjectivity positively correlates with self-efficacy in objective activity, with social self-efficacy and with the psychological well-being of an individual. It was revealed that students with low subjectivity can also have a high level of psychological well-being, while performing a compensatory function. The results obtained can be used in the course of student training, as well as in the work of curators of student groups and in the activities of the psychological service of universities.